Adaptive power-aware prefetch in wireless networks. - Liangzhong Yin (IEEE Transactions on wireless communications)
Most of the prefetch techniques used in the current cache management schemes do not consider power constraints of the mobile clients and other factors such as the size of the data items, the data access rate, and the data update rate. In this paper, we address these issues by proposing a power-aware prefetch scheme, called adaptive value-based prefetch (AVP) scheme. The AVP scheme defines a value function which can optimize the prefetch cost to achieve better performance. Also, AVP dynamically adjusts the number of prefetches to get better tradeoff between performance and power. As stretch is widely adopted as a performance metric for variable-size data requests, we show by analysis that the proposed approach can indeed achieve the optimal performance in terms of stretch when power consumption is considered. Simulation results demonstrate that our algorithm significantly outperforms existing prefetching algorithms under various scenarios.